Efektivitas Multimedia Interaktif Padlet Terhadap Kemampuan Penyelesaian Masalah Matematis Siswa SMK Karya Nasional Kuningan - Nur’rochim, Hendri; Umbara, Uba (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effectiveness of Padlet interactive multimedia in improving students' mathematical problem-solving skills. This study uses quantitative research, with a Nonequivalent Pretest-Posttest Control Group Design. The use of experimental research aims to determine the effect of certain variables on other variables. This design uses two experimental classes. This research will be conducted at SMK Karya Nasional Kuningan with the research subjects being 10th grade students of SMK Karya Nasional Kuningan in the 2024/2025 academic year. The data collection technique used in this study is a test. The research instrument used is in the form of essay questions. In this study, the test used is the Mann Whitney U test. The results of the study show that Padlet interactive multimedia has a very high level of validity and practicality. In addition, data analysis shows a significant difference in students' mathematical problem-solving abilities between the experimental class and the control class. Thus, Padlet interactive multimedia can be used as an alternative interactive learning multimedia in mathematics learning.